2011
DOI: 10.4161/gmcr.2.3.18003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro root induction of faba bean ( Vicia faba L.)

Abstract: A dose-effect relationship has been established for high-energy neutrons (maximum energy 600 MeV) within a dose range of 0.2 to 80 cGy and for low-energy neutrons produced by a 252 Cf source (mean energy 2.35 MeV) for doses between 0.2 and 5 cGy. The number of micronuclei produced by neutron radiations was found to increase linearly with dose. The Relative Biological Effectiveness (RBE) values calculated using 6 °Co radiation as a reference were, in the high-dose ·region, 4.7 ± 0.4 and 11.8 ± 1.3 for the high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In a micro propagation system, the final culture stage prior to acclimatization is rooting (Ismail et al, 2011;Millán-Orozco et al, 2011). Survival of in vitro grown plantlets in the field depends on the development of a good rooting system to absorb water and nutrients from the soil (Benková and Bielach, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In a micro propagation system, the final culture stage prior to acclimatization is rooting (Ismail et al, 2011;Millán-Orozco et al, 2011). Survival of in vitro grown plantlets in the field depends on the development of a good rooting system to absorb water and nutrients from the soil (Benková and Bielach, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…VILLORDON et al (2009) observed the adventitious root development, and suggested the initial stages of adventitious root development are critical in determining storage root set in sweetpotato. ISMAIL et al (2011) proved that the produced roots are initiated as the adventitious lateral root with tri-arch xylem strands as compared with the pentaarch of the primary roots of the intact faba bean seedling. MILLÁN-OROZCO et al (2011) observed the process of adventitious root formation with the eigthweek-old shoots of Cedrela odorata.…”
Section: Introductionmentioning
confidence: 98%
“…The fundamental concept in a micropropagation system revolves around acclimation, with the final stage of the culture process referred to as rooting (Ismail et al, 2011;Millán-Orozco et al, 2011). In order to thrive in natural settings, in vitro-generated plantlets need a robust root system that contributes to the soil's absorption of water and nutrients (Benková & Bielach, 2010).…”
Section: Introductionmentioning
confidence: 99%